Work Life Balance – Work or Home? Why Not Both? Exploring the Challenges and Progress in Achieving Work-Life Balance for Women in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Women in India have always been given a choice Do you want to marry and settle down or have a career? Why not both? Why can’t she have a family and still be a CEO of an MNC? Why can’t she cook rotis and still be a Nuclear Space Scientist? Why not? From time eternity women, they say, know how to strike a balance – be it work and home OR in laws and parents. She is the best juggler, the best source to manage time, the best powerhouse of resource. However, it has been impacting her health now, with stress at work, managing home, kids, and parents and in law seems to taking a toll on her health. Many organisations are working to provide a Balance in work life and their personal lives. But the gap still seems to be way too much to bridge. Most of the work life balance policies are evidently seen in new age organisations – IT companies, Multi nationals and the likewise. For other non-contemporary Organisations there is still a long way to go to consider Work life balance practices as Strategic Human Resource initiative.